We have always lived in the castle - Jackson, Shirley, 1916-1965 (Penguin classics deluxe edition., 2006)
"Merricat Blackwood lives on the family estate with her sister Constance and her uncle Julian. Not long ago there were seven Blackwoods -- until a fatal dose of arsenic found its way into the sugar bowl one terrible night. Acquitted of the murders, Constance has returned home, where Merricat protects her from the curiosity and hostility of the villagers. Their days pass in happy isolation until cousin Charles appears. Only Merricat can see the danger, and she must act swiftly to keep Constance from his grasp"--Publisher's description.